Correction: Cyclopeptidic photosensitizer prodrugs as proteolytically triggered drug delivery systems of pheophorbide A: part II – co-loading of pheophorbide A and black hole quencher. Issue 11 (23rd October 2019) - Bouilloux, Jordan; Yushchenko, Oleksandr; Dereka, Bogdan; Boso, Gianluca; Babič, Andréj; Zbinden, Hugo; Vauthey, Eric; Lange, Norbert
Abstract : Correction for 'Cyclopeptidic photosensitizer prodrugs as proteolytically triggered drug delivery systems of pheophorbide A: part II – co-loading of pheophorbide A and black hole quencher' by Jordan Bouilloux et al., Photochem. Photobiol. Sci., 2018, 17, 1739–1748.